Research and Medical Transcranial Doppler System - Marcin LEWANDOWSKI; Mateusz WALCZAK; Piotr KARWAT; Beata WITEK; Paweł KARŁOWICZ (Archives of Acoustics)
A new ultrasound digital transcranial Doppler system (digiTDS) is introduced. The digiTDS enables diagnosis of intracranial vessels which are rather difficult to penetrate for standard systems. The device can display a color map of flow velocities (in time-depth domain) and a spectrogram of a Doppler signal obtained at particular depth. The system offers a multigate processing which allows to display a number of spectrograms simultaneously and to reconstruct a flow velocity profile.